2017
DOI: 10.18520/cs/v113/i02/317-322
|View full text |Cite
|
Sign up to set email alerts
|

Ants Indicate Urbanization Pressure in Sacred Groves of Southwest India:A Pilot Study

Abstract: A ready reckoner of fertilizer doses has been prepared considering different yield targets at different fertility status of the soils (Table 4) which will be useful for extension officers, scientists and farmers alike in balanced fertilization of crop for targeted yield. These equations will be useful in red, laterite and yellow soils (Inceptisols and Alfisols) which constitute 84% of the total geographical area of Odisha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Regardless of the locations, the sacred groves contain relics of evergreen forests of the size < 10 ha. While the floristic aspects of the biodiversity of the sacred groves of these States are well-known 36,37 , with our investigations, the faunistic aspects of the biodiversity of the sacred groves are just coming to the light 30,31,34,[38][39][40] . While the sacred groves of Kodagu are located on a land mosaic of human settlements, business districts, homeyards, coffee plantations, and protected forests, the sacred groves of Kasaragod and Trivandrum are located on a land matrix of human settlements, business districts, and Coconut-based orchards or homeyards.…”
Section: Sacred Grovesmentioning
confidence: 60%
See 2 more Smart Citations
“…Regardless of the locations, the sacred groves contain relics of evergreen forests of the size < 10 ha. While the floristic aspects of the biodiversity of the sacred groves of these States are well-known 36,37 , with our investigations, the faunistic aspects of the biodiversity of the sacred groves are just coming to the light 30,31,34,[38][39][40] . While the sacred groves of Kodagu are located on a land mosaic of human settlements, business districts, homeyards, coffee plantations, and protected forests, the sacred groves of Kasaragod and Trivandrum are located on a land matrix of human settlements, business districts, and Coconut-based orchards or homeyards.…”
Section: Sacred Grovesmentioning
confidence: 60%
“…Invasion of tramp or invasive species results in colonization and spill-over to neighbouring less-disturbed areas, where they might displace or affect the activities of native ants 15,30,32,33 . Our pilot studies showed that the plausible native, but globally notorious invasive ant species, the Yellow-Crazy Ant (Anoplolepis gracilipes), increased several folds in urban sacred groves and spilled over to the rural sacred groves of northern Malabar region over a period of 6 years 30,34 . Conversely, in the southern United States, the invasive fire ant-Solenopsis invicta-translocated the native fire ant-S. geminata-from the natural forests to urban green spaces 33 .…”
mentioning
confidence: 85%
See 1 more Smart Citation